Millennium development goals: impact of sustainability discourses, conflict and inter-governmental actions on the built environment (2015)
As part of the Millennium Cities initiative, organized by Earth Institute of Columbia University USA, Akure, Nigeria was selected as one of the cities in Sub-Saharan Africa to be assisted in achieving the millennium development goals (MDGs). Other cities selected in Sub-Saharan Africa include Kisumu. (Kenya); Blantvre. (Malawi); Kumasi, (Ghana); Bamako. (Mali); Sezou, (Mali); Kaduna, (Nigeria) and Mekelle. (Ethiopia). It is necessary to point out that this initiative focuses more on inter-governmental actions than tackling the source of the developmental problem of the cities involved in the initiative. Using a mixed methodological approach, which included participant observation and structured interviews by means of convenience and snowball sampling methods administered in the study area. According to the aim of the project it is to promote investment from overseas (capitalist) companies, create employment and help in the domestic affairs of the cities involved. This paper examine the impact of the MDGs on the built environment and critique these ‘lofty ideas' which has failed to address the local, regional and cultural specificity of the location; and which has not been productive in Sub-Saharan Africa. The paper concludes that the desire for an integrated city cannot be